Obesity independently predicts responders to biphasic insulin 50/50 (Humalog Mix50 and Insuman Comb 50) following conversion from other insulin regimens: a retrospective cohort study. Issue 1 (8th May 2014) - Mamza, J; Mehta, R; Idris, I
Abstract : Aims: This study aims to examine the metabolic effects of intensification or initiation of insulin treatment with biphasic insulin 50/50, and determine the predictors of responders or non-responders to biphasic insulin 50/50. Methods: A cohort of 2183 patients ≥18 years with diabetes, newly treated with biphasic insulin 50/50 between January 2000 and May 2012, were sourced from UK General Practices via The Health Improvement Network (THIN) database. Baseline clinical parameters of 1267 patients with suboptimal glycated hemoglobin (HbA1c) >7.5% (>58 mmol/mol) who had received background insulin regimens for at least 6 months preceding biphasic insulin 50/50 were compared against 12-month outcome data. Responders were defined as those with HbA1c <7.5% (58 mmol/mol) and/or HbA1c reduction of ≥1% (10.9 mmol/mol) at 12 months. Comparative analyses were carried out on subgroups of 237 patients initiating insulin therapy with biphasic insulin 50/50, and between users of the Humalog Mix50 (HM50) versus Insuman Comb 50 (IC50). Associations were examined using t tests and multivariate logistic regression techniques. Results: The overall mean HbA1c reduction at 12 months as a result of intensification and initiation with biphasic insulin 50/50 was 0.5% (5.5 mmol/mol) and 1.6% (17.5 mmol/mol), respectively. Adjusted ORs show obesity (body mass index >30 kg/m 2 ), treatment duration for ≥9 months, and baseline HbA1c are independent determinants of responders. In addition, stratified for baseline HbA1c levels, HM50 was associated with better HbA1c outcome compared with IC50. Conclusions: biphasic insulin 50/50 is effective for achieving glycemic control in suboptimal HbA1c levels, especially among obese patients with insulin-treated diabetes. Stratified for baseline HbA1c, HM50 was associated with improved HbA1c outcome compared with IC50.